Characterization of battery electric transit bus energy consumption by temporal and speed variation. (15th January 2023) - Perugu, Harikishan; Collier, Sonya; Tan, Yi; Yoon, Seungju; Herner, Jorn
Abstract: De-carbonizing transport is an important strategy for combating climate change and reducing the health impacts of air pollutants. The transit bus sector is one of the highest potential categories to be electrified with Battery-Electric Buses (BEBs). The energy consumption and fueling patterns of BEBs, however, will be different from conventional technology buses, so research is needed to better understand these phenomena to make the BEB rollout successful. We have analyzed the BEB activity and charging data collected over a year from a transit fleet (consisting of 40-ft and 60-ft BEBs) undergoing complete electrification. The average energy consumption for 40-ft and 60-ft buses were 2.6 ± 0.3 kWh/mile and 3.6 ± 0.5 kWh/mile, respectively, over the year. The regenerative braking recovered a significant amount of energy spent and that accounts for 37.3% and 40.2% of the total average energy required for 40-ft and 60-ft bus operation, respectively. Bus speed has a significant effect on average energy consumption per mile; the higher speed resulted in less energy consumption for both types of buses. The variability of seasonal and intra-day energy consumption per mile can be attributed to increased use of air conditioner (A/C) and heater, which were controlled according to the ambient temperatures. This transit agency may incur 16.2 ± 2.1% (based on current fleet composition, energy tariffs) more energy costs in Summer compared to Winter, if no optimized operation is used. This effort provides reliable BEB energy consumption estimates that can be used for any transit fleet's energy efficiency objective. Highlights: The average energy consumptions for 40-ft Buses were 2.6 ± 0.3 kWh/mile. The average energy consumptions for 60-ft Buses were 3.6 ± 0.5 kWh/mile. The regenerative braking recovered 37.3% of the total energy for 40-ft buses. The regenerative braking recovered 40.2% of the total energy for 60-ft buses. Bus speed has a significant effect on average energy consumption per miles.